Effects of smartphone restriction on cue-related neural activity - Schmitgen, Mike; Henemann, Gudrun Maria; Koenig, Julian; Otte, Marie-Luise; Rosero, Jakob P.; Bach, Patrick; Haage, Sophie H.; Wolf, Nadine D.; Wolf, Robert Christian (Computers in human behavior, 2025)
With the increasing popularity of smartphones in the past decades, physical, social, and psychological consequences of excessive smartphone use (ESU) have been increasingly debated. Cue-reactivity (CR) has been discussed as a core mechanism driving this behavior, and previous studies have highlighted distinct neural mechanisms underlying CR in individuals with ESU. Here, we used a functional MRI (fMRI) CR-paradigm to investigate the effects of smartphone restriction over 72 h in 25 young adult smartphone users. The CR-task used contrasts of images showing smartphones vs. neutral stimuli and active vs. inactive smartphones. Region-of-interest based correlations with psychometric scores were performed, and activity changes after 72 h were investigated on a neurochemical level using neurotransmitter probability maps. CR-related brain activity changes over time were most prominent in the nucleus accumbens and anterior cingulate cortex (p < 0.001). Such changes were significantly associated with dopamine- and serotonin-receptor probabilities (pFDR < 0.05). Significant associations between parietal cortex activity and craving were detected (p < 0.05). This study provides evidence for CR-related modulation of neural activity in key regions of salience, motor-inhibition, and reward processing after 72 h smartphone restriction. The identified neural mechanisms may substantially promote addictive behavior in people at risk for ESU.
Online verfügbar: 19. Februar 2025, Artikelversion: 1. März 2025
Gesehen am 18.08.2025